2021
DOI: 10.1021/acsbiomaterials.1c01230
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Formation and Mechanical Properties of Bombyx mori Silk Are Regulated by Vacuolar-Type ATPase

Abstract: The mechanism of silk fiber formation in silkworms, Bombyx mori, is of particular scientific interest because it is closely related to the mechanical properties of silk fibers. However, there are still substantial knowledge gaps in understanding the details of this mechanism. Studies have found a pH gradient in the silk gland of silkworms. A vacuolar-type ATPase (V-ATPase) is thought to be involved in establishing this pH gradient. Although it is reported that the pH gradient plays a role in silk fibrillogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…5g ; Supplementary Data 20 ). Interestingly, we found that seven ortholog gene pairs involved in the V-type ATPase family, encoding key factors involved in regulating silk fibrillogenesis 52 , were significantly upregulated in both the Duct and ASG (Fig. 5g ).…”
Section: Resultsmentioning
confidence: 96%
“…5g ; Supplementary Data 20 ). Interestingly, we found that seven ortholog gene pairs involved in the V-type ATPase family, encoding key factors involved in regulating silk fibrillogenesis 52 , were significantly upregulated in both the Duct and ASG (Fig. 5g ).…”
Section: Resultsmentioning
confidence: 96%
“…Two cuticular proteins and three V‐type ATPases were found to be enriched in the front silk gland of S. angustata , which may be related to modulation of shear stress and the pH gradient, respectively. Cuticle proteins, together with chitin, form the cuticular layer in the spinning duct, which provides shearing forces for the formation of silk fibre and contributes to the mechanical properties of silk (Wang et al, 2022), whereas V‐type ATPase in the anterior silk gland is involved in establishing the pH gradient that regulates silk fibrillogenesis and is related to the final mechanical properties of the silk fibre (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…5g; Supplementary Table 20). Interestingly, we found that seven gene ortholog pairs involved in the V-type ATPase family, encoding key factors in regulating silk fibrillogenesis 41 , were significantly upregulated in both the Duct and ASG (Fig. 5g).…”
Section: Convergent Evolution Of the Tri-section Silk Gland Between T...mentioning
confidence: 96%